Structural basis for the selective inhibition of HDAC10, the cytosolic polyamine deacetylase - Herbst-Gervasoni, Corey J.; Steimbach, Raphael R.; Morgen, Michael; Miller, Aubry K.; Christianson, David W. (ACS chemical biology, 2020)
The cytosolic class IIb histone deacetylase HDAC10 is an emerging target for drug design. As an inducer of autophagy, its selective inhibition suppresses the autophagic response that otherwise attenuates the efficacy of cytotoxic cancer chemotherapy drugs. HDAC10 is a zinc-dependent polyamine deacetylase exhibiting maximal catalytic activity against N8-acetylspermidine. As revealed in the structure of Danio rerio (zebrafish) HDAC10, two conserved structural motifs direct this narrow substrate specificity: a 310 helix containing the P(E,A)CE motif that sterically constricts the active site and an electrostatic “gatekeeper,” E274, that confers selectivity for cationic polyamine substrates. To accelerate drug design efforts targeting human HDAC10, we now report the preparation of “humanized” zebrafish HDAC10 in which two amino acid substitutions, A24E and D94A, yield an active site contour more similar to that of human HDAC10. X-ray crystal structures of this HDAC10 variant complexed with Tubastatin A and indole analogues bearing pendant tertiary amines reveal that inhibitors capable of hydrogen bonding with gatekeeper E274 exhibit high affinity and selectivity for HDAC10 over HDAC6 (the other class IIb isozyme). Moreover, these structures reveal that the P(E,A)CE motif helix can shift by up to 2 Å to accommodate the binding of bulky inhibitors. Thus, slender polyamine-like inhibitor structures are not exclusively required for selective, high affinity binding to HDAC10. Indeed, the flexibility of the P(E,A)CE motif helix could conceivably enable the binding of certain protein substrates.
Gesehen am 15.10.2020